BCL11A Promotes the Progression of Laryngeal Squamous Cell Carcinoma - Zhou, Jian; Zhou, Liang; Zhang, Duo; Tang, Wei-Jing; Tang, Di; Shi, Xiao-Ling; Yang, Yue; Zhou, Lin; Liu, Fei; Yu, Yong; Liu, Pentao; Tao, Lei; et al. (Frontiers in Oncology, 2020)
Background: We report functional and clinical data uncovering the significance of B-cell lymphoma/leukemia 11A (BCL11A) in laryngeal squamous cell carcinoma (LSCC). Methods: We examined BCL11A expression in a cohort of LSCC patients and evaluated the association between BCL11A expression and clinicopathological features. We investigated the consequences of overexpressing BCL11A in the LSCC cell line on proliferation, migration, invasion, cell cycle, chemosensitivity, and growth in vivo. We explored the relationship between BCL11A and MDM2 in LSCC and tumorigenesis pathways by using the Human Cancer PathwayFinder Array. Results: High levels of BCL11A were found in LSCC tissues and were more frequently associated with advanced lymphatic metastasis stages with poor prognoses. BCL11A overexpression enhanced LSCC proliferation in vitro and vivo. A positive correlation between MDM2 and BCL11A expression was identified. Conclusions: These data uncover important functions of BCL11A in LSCC and identify BCL11A as a prognostic biomarker and potential therapeutic target in LSCC.